ANALISIS KEMAMPUAN SISWA DALAM MENYELESAIKAN SOAL MATEMATIKA - Rencitia (MEGA: Jurnal Pendidikan Matematika, 2024)
The objectives of this study are to determine the level of students ability in solving math problems In this study , the method used is a quantitative method. Quantitative data was obtained from this research from the answers collected by student. The results obtained indicate that Analysis of items in Mas Koto Rendah most student are not able to complete both multiple-choice question atan essay..